The Influence of Relationship Marketing, Service Quality, and Customer Satisfaction on Customer Loyalty Over B2B Companies - Ikraman Ikraman; Tantri Yanuar R. Syah (Penerbit Kemala Indonesia, 2019)
Customer loyalty is very important in a company to retain customers with customer loyalty function to reduce competition between competitors and reduce marketing costs. Customer loyalty can be affected by relationship marketing, service quality, and customer satisfaction. This study aims to find out how the influence of relationship marketing, service quality and customer satisfaction toward customer loyalty at PT. Alam Neur Nusapermai. In this study, we used a questionnaire which was distributed to 145 customers at PT. Nusapermai Neur, Nature of the data processed using SPSS 23 and AMOS 23. Here, we use secondary and primary data also data analysis using the SEM method. The result indicates that relationship marketing does not affect customer satisfaction, quality services to customer satisfaction, but satisfaction does not influence toward customer loyalty, relationship marketing does not have an effect on customer loyalty and service quality does not affect customer loyalty.